Teachers Perception, Usage of Community Resources in Social Studies and Civic Education, Delta State, Nigeria - Atubi, Onamrewho Favour (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2021)
The study aimed at reporting the perception and usage of community resources by Social Studies and Civic Education teachers in Delta State, South South, Nigeria. Two research questions and one hypothesis were raised to give the study a direction. A sample of 196 out of a population of 656 Social Studies and Civic Education teachers was used for this study. Instrumentation was done with researcher’s designed questionnaire with a reliability index of 0.89. Data was analyzed with percentage for research questions and Analysis of Variance (ANOVA) was used to test the hypothesis of the study. Findings of the study demonstrated that Social Studies and Civic Education teachers of public schools in Delta State perceive the use of community resources to be high for effective teaching but usage of the resources was relatively low. Hence the study concluded by recommending that spirited effort be made by all the stakeholders involved to employ the judicious use of community resources for Social Studies and Civic Education instructions in secondary schools of Delta State.